Meninjau pemahaman mengenai ari-ari (plasenta) bayi di desa sukadame kecamatan tigapanah dari perspektif dogmatika - Josua Ardian Mahesa Simanungkalit; Pardomuan Munthe (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
This study was motivated by the continuing practice of treating a newborn's placenta (ari-ari) in the customs of the Karo ethnic group, which is understood by some members of the community as having spiritual protective significance. This study employed a qualitative descriptive method through interviews and questionnaires conducted among the residents of Sukadame Village. The purpose of this study was to analyze the community's understanding of the practice of treating a newborn's placenta in Karo culture and to examine it based on the doctrine of God's providence from a Christian theological perspective. The findings indicate that some members of the community continue to associate this practice with the protection of infants, thereby potentially shifting their dependence away from God. Based on the observations conducted by the researcher, this study concludes that the primary issue lies in the community's understanding rather than in the culture itself. Therefore, the church needs to provide contextual and continuous theological guidance.